Oral Corrective Feedback and Students’ Oral Participation: A Micro-Ethnographic Analysis in Arabic Qira’ah Learning - Abdurrahman Ahmad Agil (Dzihni: Jurnal Pendidikan Bahasa Arab, Linguistik dan Kajian Literatur Arab, 2026)
The purpose of this study is to explain and analyze the OCF used by teachers and its effect on the oral participation of students in learning the Arabic language at the Islamic Junior High School level. The qualitative research method was used for the analysis of natural communication occurring in the event of tashih qira’ah (reciting the recitation of Arabic). Data were collected through participant observation (video-audio recordings of six meetings), stimulated recall interviews, field notes, and document analysis. Participants consisted of two Arabic teachers and eight students selected purposively. Data analysis was conducted through verbatim transcription, identification of OCF (trigger-error-feedback-uptake) episodes, thematic coding, and the preparation of thick descriptions. We found more instances of explicit correction and recast with immediate timing. Uptake by learners followed different patterns, with successful repair often found in elicitation methods, while repetition often does not get a response, accompanied by non-verbal actions such as silence and lowering the head. Furthermore, peer repair practices were found to involve other students in the correction process. In terms of participation, OCF resulted in an uneven distribution of speaking opportunities and the emergence of avoidance strategies among some students. The implication in these results is that OCF can be considered as a form of corrective activity, in addition to being a factor that influences interactions and emotional elements in the classroom environment. Keywords: oral corrective feedback, oral participation, micro ethnography.